Optimization of Property Tax Revenue: A Case Study in Klaten, Indonesia - Faizah Khotimatul Husna; Elsi Puspito Anggraini; Arie Rachma Putri (Urecol Journal. Part G: Multidisciplinary Research, 2021)
The research aims to analyze the implementation of collection of land and building tax, optimization of PBB’s revenue and factors that influence the optimization of PBB’s revenue in Kelurahan Klaten, Kecamatan Klaten Tengah, Kabupaten Klaten. The method in this study uses a qualitative approach to the type of descriptive research. The data used are primary’s data and secondary’s data for 2015 - 2018. Primary’s data were obtained from direct interviews with stakeholders namely the apparatus or team of Land and Building Tax’s collection officers. Secondary’s data is taken from revenue’s data from the principal provisions of the PBB, the principal’s data on the provisions of PBB, and honorarium’s data of the PBB’s collection, the data are processed and processed using the formula of the ratio of effectiveness and efficiency. The results showed that the implementation of the Taxation of Land and Building Tax in Kelurahan Klaten had been run with a well-structured governance so that the revenue of the Land and Building Tax in 2015 - 2017 which was initially running quite optimally had increased in 2018 ie running optimally this was influenced by two good factors that come from the attitude of the apparatus or team of Land and Building Tax’s collection officers or awareness of taxpayers. Based on the results of the above understanding, the authors can provide suggestions related to efforts to increase optimization of PBB’s revenue that the Kelurahan Klaten in order to maximize the collection process through increasing counseling and hold a ball pick-up system every month, impose the application of policies for taxpayers through administrative requirements that require the inclusion of the PBB’s paid off in every service and punishment the sticking of a PBB’s sticker has not been paid off in every home. And the taxpayers are expected to have the awareness to pay taxes on time.